(untitled) (Scientific journal of the Fergana State University, 2023)
Chemical, hydrolysis, coal mining, petrochemical, food and other industries in the field of their activities for several years along with obtaining targeted products "produce" hundreds of millions of tons of waste, the disposal of which, as a rule, is out of sight of existing enterprises. As a result, natural resources are depleting, the environment pollutes all kinds of waste, emissions of harmful substances into water, atmosphere and soil.